Enhancing access to innovative cancer drugs: Cross-sector consensus on a way forward to benefit patients. Issue 4 (April 2022) - Hoey, Richard; Sharpe, Eva; Kukula, Angela; Workman, Paul
Highlights: New discoveries are driving advances in our understanding of cancer and its evolution. But progress has been uneven and new drugs are difficult for healthcare systems to afford. We need greater flexibility in how new drugs are priced so costs and risks can be shared. Regulators and industry should agree methodologies for early evaluation of drugs. We must incentivise the creation of mechanistically novel cancer drugs and combinations. Abstract : New discoveries and technologies are driving major advances in our understanding of cancer and underpinning a new era of precision medicine and immunotherapy. However, advances in treatment have been uneven: whereas survival rates for some common cancers are improving rapidly, for others there has been much less progress. In addition, healthcare systems are finding it difficult to provide access to expensive new treatments. There is an urgent need for imaginative policy solutions to incentivise the creation of novel therapies that address the full range of cancer-causing mechanisms. We have worked with organisations across the medical research community to develop consensus statements on how to enhance access to innovative cancer drugs. Here, we present our reflections on these statements.